2019
DOI: 10.1038/s41467-019-11939-7
|View full text |Cite
|
Sign up to set email alerts
|

Active control of viscous fingering using electric fields

Abstract: Viscous fingering is a widely observed phenomenon, in which finger-like instabilities occur at the interface of two fluids, whenever a less viscous phase displaces a more viscous phase. This instability is notoriously difficult to control, especially for given viscosity ratio and geometry. Here we demonstrate experimentally the active control of viscous fingering of two given liquids, for given geometry and flow rate in a Hele-Shaw cell. The control is realized by taking advantage of electro-osmotic flows alon… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
54
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 61 publications
(55 citation statements)
references
References 64 publications
1
54
0
Order By: Relevance
“…The size of the vasculature was consistently approximately 600 µm wide and 100 µm tall. Notably, the collagen channel contained geometrical irregularities due to the interfacial instability during the viscous fingering process [ 43 ]. In the formed vascular lumen, some regions in the confocal slices appeared to be darker than the surrounding regions ( Figure 3 A,C), which were due to the difference in focus and contrast caused by the irregular wall shapes in the continuous endothelial layer ( Supplemental Figure S1 ).…”
Section: Resultsmentioning
confidence: 99%
“…The size of the vasculature was consistently approximately 600 µm wide and 100 µm tall. Notably, the collagen channel contained geometrical irregularities due to the interfacial instability during the viscous fingering process [ 43 ]. In the formed vascular lumen, some regions in the confocal slices appeared to be darker than the surrounding regions ( Figure 3 A,C), which were due to the difference in focus and contrast caused by the irregular wall shapes in the continuous endothelial layer ( Supplemental Figure S1 ).…”
Section: Resultsmentioning
confidence: 99%
“…Moreover, this large‐scale control of membrane flow would be applicable to studies of membrane instability under an electric field at micro‐ and nanoscale levels, considering that recent studies have enabled active control of viscous‐fingering by an electric field. [ 47,48 ]…”
Section: Resultsmentioning
confidence: 99%
“…Similarly, in template-assisted electrodeposition, [75][76][77][78] it may be possible to tune the symmetry of dendritic patterns by varying the strength of diffusion anisotropy in the electrolyte domain. Active control of anisotropic dendritic growth may also be achieved, for example, by applying electric fields to control viscous fingering 18,19 over patterned, charged surfaces 79 having anisotropic electro-osmotic slip tensors. 80…”
Section: Discussionmentioning
confidence: 99%
“…The phenomenon of viscous fingering has played an important role in elucidating the basic principles of these two types of growth, [12][13][14][15] as well as methods to control the resulting patterns. [16][17][18][19][20][21][22][23][24][25][26][27] Viscous fingers result from the Saffman-Taylor instability, when one fluid is displaced by another less viscous one in the quasi-two dimensional geometry of a Hele-Shaw cell. 28,29 It has been shown that dendritic growth requires anisotropy in the interfacial dynamics.…”
Section: Introductionmentioning
confidence: 99%